(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The research titled "The Influence of Glass and Aluminium Composite Panel Building Envelopes on Indoor Temperature Rise" explores the impact of building envelope materials on indoor temperature variations. Conducted at the Central Laboratory Building of Diponegoro University, the study evaluates the efficacy of glass and ACP materials in reducing heat ingress during periods of inactivity. Through quantitative analysis and field observations, the research identifies significant temperature reductions when these materials are combined with brick walls. Findings suggest optimal orientations for minimizing heat gain and enhancing energy efficiency. The study concludes by providing recommendations for building design and future research directions. This innovative research contributes valuable insights to architectural knowledge and sustainable building practices.